Controllability of road vehicles at the limits of tyre adhesion - Kohn, Heinz Joachim (Cranfield University, 1998)
The research project 'Controllability of Road Vehicles at the Limits of Tyre Adhesion' (CROVLA) was established to investigate how tyre and chassis properties contribute to the handling characteristics and stability of vehicles operating at or near to the limit condition. The project involved the Department of Transport, SP Tyres UK Limited, Jaguar Cars and Cranfield University. An extensive proving ground test program of typical limit handling tests provided characteristic driver input and vehicle response data for a variety of vehicle configurations. The test data analysis was based on the concept of correlation. Cross- correlation coefficients and average response time delays were obtained for various pairs of quantities, namely steering angle and torque for the input and yaw rate and lateral acceleration for the response. The predictability of the vehicle response was evaluated by the rate by which the correlation coefficients change with severity. Analogous to the proving ground work, vehicle dynamics simulations were carried out. Two programs were employed to study the steady state performance and the transient limit handling behaviour. The `Steady State Cornering Model' was used to confirm some basic suspension design rules established for optimising the lateral adhesion of a suspension design. The importance of controlling camber and vehicle jacking by an appropriate suspension design was identified. A detailed vehicle model was built-up using the simulation code AUTOSIM. After validating the model against proving ground data, some parametric studies were conducted to quantify the effects of suspension and tyre properties on the transient limit response behaviour. Proving ground and simulation results suggest that response time lags and cross- correlation coefficients in combination with other handling parameters can be used as objective quality measures. The results quantified to what extent tyre and chassis modifications change the limit handling behaviour.